Epidemiological assessment of Respiratory Syncytial Virus infection in hospitalized infants, during the season 2005-2006 in Palermo, Italy - Collura Mirella; Dones Piera; Fucà Fortunata; Poma Antonella; Gueli Alessandra; Salsa Ludovico; Romano Amelia; Di Carlo Paola; Pampinella Diego; Motisi Delia; Corsello Giovanni (BMC, 2009)
Abstract Objectives Respiratory Syncytial Virus (RSV) is the leading cause of hospitalization for lower respiratory tract infections (LRTI) in young children worldwide. We evaluate the epidemiological and clinical patterns of RSV infection in infants hospitalized for LRTI in in Palermo, South Italy, Sicily. Methods We collected the demographic details of infants hospitalized to G. Di Cristina Children's Hospital in Palermo for LRTI between November 2005 and May 2006. We also included all cases occurred in newborns hospitalized in the Neonatal Intensive Care Unit (NICU) Of Palermo. Results During the studied period, 335/705 hospitalized infants for LRTI were enrolled in the study. The trend of hospitalization started in late winter and lasting until May 2006 with an epidemic peak in spring. 178/335 infants tested for viral infection showed RSV disease. Three cases occurred in preterm newborns hospitalized from birth in NICU. The likelihood to be RSV+, rather than RSV negative (RSV-) was higher for infants < 6 months and lower for infants with history of breast feeding (P < 0.05). RSV infection was associated with a higher likelihood to be admitted to intensive care unit and to a longer hospitalization and oxygen therapy. Conclusion The study shows that, in Sicily, RSV is an important cause of LRTI in infants. The seasonal distribution shows that both LRTI and RSV infections peak in late spring, in contrast to Northern Italy. Our data could help to define the regional appropriate start of prophylactic interventions.